The intellectual activities of the Maghreb cinematic discourse: Attempts to understand reality and its manifestations - Elmahmoudi, Tarek Mohammed (Journal of Humanities & Social Sciences, 2023)
Maghreb cinema is one of the most important Arab and African cinemas that has paid extreme thoughtfulness to the intellectual content inside the making of feature films. This content was arranged through a cinematic language whose expressions were grounded on predominantly aesthetic concepts. These perceptions therefore established the specificity and uniqueness of this cinema. This trend led to the presentation of a cinematic discourse of reformist dimensions, reflecting the level of cinematic awareness that filmmakers have in this geographical arena. These filmmakers have the ability to develop creative concepts that respond to the aspirations of the viewer and establish the vivacity of this sector. This discourse has been linked to the local reality in its political and social transformations thus interpreting the artistic revelations of the directors, and also shaping the scope that determines the course of the cinema.On the other hand, the conceptual theses of this discourse and its work faced many difficulties, which hindered the aspirations and dreams of Maghreb film directors. These hindrances varied according to time and place. In brief, finding solutions to release the Maghreb cinematic act, and its creativity is so necessary. This liberation embodies the central instrument that could enhance the whole cinematic process.
Keywords: Maghreb cinema; discourse; intellectual works; creative act; reality